Thrombocytopenia in end-stage renal disease and chronic viral hepatitis B or C - Olga Hilda Orasan; Laura Urian; George Ciulei; Iulia Breaban; Andreea Maria Stefan; Sorina Cezara Secara; Adela-Sitar Taut; Simina Tarmure Sarlea; Vasile Negrean; Dorel Sampelean; Ioan Mihai Patiu; Remus Aurel Orasan; et al. (Journal of Mind and Medical Sciences)
Objectives. We evaluated platelet counts in end-stage renal disease and chronic viral hepatitis. Materials and Methods. We studied 70 patients with end-stage renal disease and chronic viral hepatitis and compared them to a control group of 45 patients without hepatitis. Results. The presence of viral hepatitis was associated with a higher prevalence of thrombocytopenia. Correlations between age, C-reactive protein, liver stiffness measurement, and platelet count were observed. C-reactive protein levels > 10 mg/dl were associated with a lower risk of thrombocytopenia in patients with end-stage renal disease and chronic viral hepatitis, yet age > 60 years, dialysis vintage > 10 years, aspartate and alanine aminotransferase levels > 20 IU/L, albumin levels < 3.5 g/dl, and fibrosis stage ≥ 3 were not related. Conclusions. Chronic viral hepatitis leads to a higher prevalence of thrombocytopenia. Platelet counts in these patients begin to decrease significantly once liver fibrosis reaches stage III.